Geothermal energy and the public: A case study on deliberative citizens' engagement in central Italy. (February 2017) - Pellizzone, Anna; Allansdottir, Agnes; De Franco, Roberto; Muttoni, Giovanni; Manzella, Adele
Abstract: This paper reports on a case study on the citizens' engagement with developments towards the harnessing of geothermal energy in central Italy. The research has been conducted within the framework of a larger project on the feasibility of further geothermal developments in Italy, funded by the Italian government. The aims of the case study research were first to explore the role of public and stakeholder engagement in the processes of innovation in the geothermal energy sector. Second, to design, implement and consolidate a methodological framework for comparative analysis of case studies on citizens' engagement, thus bringing a social scientific perspective into geothermal energy research. The results show general support for renewable energy but knowledge and understanding of the potential of geothermal is remarkably low. Lack of trust in politics and unsure public communication emerged as prominent themes where the common good and community developments are sharply contrasted with corporate and private interests. As geothermal energy is included and encouraged under the European Strategic Energy Plan and in the Paris agreement on halting climate change, the results can make significant input into future policy making, by providing concrete guidelines on citizens' engagement in processes of culturally sustainable innovation. Highlights: Original research, case study on citizens' engagement with geothermal energy. Considerable public uncertainty over geothermal energy. Information is a key issue for all stakeholder and citizens cooperation in the energy sector. Everyday notions of "the common good" strongly shape community discussions about energy. Geothermal energy developments need to take the views of communities into account.